Caracterización funcional de almidones de plátano cuadrado (Musa balbisiana Colla) - Contreras-Pérez, Roxana Karina; Torre-Gutiérrez, Lázaro De la; González-Cortés, Nicolás; Jiménez-Vera, Román (European Scientific Journal, ESJ, 2018)
Resistant starch (RS) stands out for its properties related to human health. In the digestive system it provides the benefits of dietary fiber and acts as a prebiotic. New sources of resistant starch are being investigated. The proximal composition, functional properties and microbiological quality of square banana starches (Musa balbisiana Colla) were determined. The fruits were harvested in plantations of Tabasco, Mexico, with degree of maturity type I. The flour was elaborated by drying in an oven. The extraction of the starches was carried out using a wet method and the resistant starches, by enzymatic method. The concentration of bacterial groups was quantified by the surface culture method. The solubility, swelling power and water absorption patterns were evaluated at 60, 70, 80 and 90 ºC. Products with low moisture content were obtained: flour (7.45 ± 0.28), native starch (9.28 ± 0.55) and sterilized starch (10.82 ± 0.10). In the protein content, the highest concentration was observed in the flour (4.44 ± 0.40), followed by the native starch (1.19 ± 0.04), RS2 (0.13 ± 0.01) and RS3 (0.19 ± 0.01). Functional properties are related to different factors, such as temperature, granule size, amylose content and type of resistant starch. RS3 presented the best functional properties and good microbiological quality. The native starch presented the highest microbial load. RS2 and the sterilized starch presented the lowest values of the functional properties.